Redistribution Policy and Social Welfare: A View from Macroeconomics (2022)
This paper evaluates the effects of redistribution policies on macroeconomic performance, income distribution and social welfare using three alternative social welfare criteria (Pareto's, Rawls' and a mixed one), and establishes the link between the above and the ruler's optimal policy. The main conclusions are the following: 1) a negative effect of redistribution through taxation and subsidies is the increase in the interest rate; 2) as a society advances in the process of wealth redistribution, there comes a time when the ruler faces a trade-off: to maintain this process or to avoid losses in social welfare.